Oil extraction from seeds of Carica papaya L.: Obtaining the lipid profile and thermal evaluation - Fonseca, Mariana; Kobelnik, Marcelo; Fontanari, Gustavo Guadagnucci; Crespi, Marisa Spirandeli; Ribeiro, Clóvis Augusto (Eclética Química, 2023)
Carica papaya L. is frequently found in northern and northeastern Brazil, the Caribbean and Central America. The papaya seed oil was extracted using Soxhlet extraction. Its oil has low acidity, iodine index, saponification and peroxide values adequate and comparable to other commercially available vegetable oils. The lipid profile of this oil was also obtained by gas chromatography; thermal characterization was performed by thermogravimetry (TG) and differential scanning calorimetry (DSC) under various heating rates. The composition of the in-nature oil indicates that oleic and palmitic fatty acids are predominant. The DSC analysis under cooling shows that the crystallization phase of this oil is similar to olive oil, and the thermogravimetric results show the thermal decomposition under nitrogen purge gas occurs in only one stage. The activation energy was obtained applying the isoconversional methods proposed by Capela and Ribeiro, Ozawa and Friedman. The obtained kinetics data leads to a dependence on the sample mass and purge gases, which results in several kinetic patterns.